La eficacia del test de igualdad para asegurar el cumplimiento del principio de igualdad y no discriminación - Rúales Amay, María de los Ángeles (2024)
In this Curricular Integration Work is entitled: The effectiveness of the equality test to ensure compliance with the principle of equality and non-discrimination, whose interest in developing this legal problem is based on analyzing whether the test is being well applied, is effective in all cases for which this test is applied or is not being effective and in this way each of its components, characteristics and the test of equality and non- discrimination is thoroughly analyzed. Likewise, legal regulations are taken into account, taking into consideration as a specific case to analyze the rights of first year students of higher education institutions to exercise the right to vote in the election of authorities. This topic addresses the fight against discrimination and inequality in Ecuadorian legislation, focusing on the equality test as a key tool for evaluating the conformity of norms and legal acts with the principle of equality and non-discrimination. Relevant cases, such as Ruling No. 7-11-IA/19 and Ruling No. 14-21-IN/21, are examined to explore the effectiveness of the test in diverse situations, from merit competitions to university electoral processes. Through this study, we seek to understand the ability of the equality test to prevent discrimination in a comprehensive manner and to address the complexities that could generate inadvertent exclusions in Ecuadorian society.